2017
DOI: 10.1002/prp2.336
|View full text |Cite
|
Sign up to set email alerts
|

Prevention against renal damage in rats with subtotal nephrectomy by sacubitril/valsartan (LCZ696), a dual‐acting angiotensin receptor‐neprilysin inhibitor

Abstract: Although patients with chronic kidney disease (CKD) are at increased risk for end‐stage renal disease and cardiovascular events, adequate drug therapies for preventing the deterioration of these conditions are still not established. This study was undertaken to evaluate a preventive effect of an angiotensin receptor‐neprilysin inhibitor sacubitril/valsartan (LCZ696), which is converted to sacubitril and valsartan in the body, against the progression of renal disease in rats with subtotal nephrectomy, an animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Therefore, some recent pre-clinical studies have begun to explore the mechanisms underlying the renoprotective effects of this drug combination. In this regard, two recent studies demonstrated superior renoprotection with sac/val compared to val monotherapy in rat models of severe CKD due to subtotal nephrectomy [ 56 , 57 ]. In the present study, we examined the effects of sac/val on glomerular, i.e ., filtration barrier injury, as well as, tubular remodeling and kidney fibrosis, along with associated changes in biochemical parameters in ZO rats, a translationally relevant model of early stage DN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some recent pre-clinical studies have begun to explore the mechanisms underlying the renoprotective effects of this drug combination. In this regard, two recent studies demonstrated superior renoprotection with sac/val compared to val monotherapy in rat models of severe CKD due to subtotal nephrectomy [ 56 , 57 ]. In the present study, we examined the effects of sac/val on glomerular, i.e ., filtration barrier injury, as well as, tubular remodeling and kidney fibrosis, along with associated changes in biochemical parameters in ZO rats, a translationally relevant model of early stage DN.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we observed that sac/val was more effective in lowering plasma total cholesterol compared to val or hydralazine. Since hypercholesterolemia in diabetes is usually associated with increased oxidized LDL and renal injury [ 57 , 61 ], it is possible that the improvement in plasma total cholesterol in ZOSV may have contributed, in part, to amelioration of kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopeptidase inhibitors had shown promise as a treatment for chronic kidney disease in animal models, but as previously discussed, clinical development of this class of drugs was discontinued (35). Sacubitril/valsartan is now being studied as a potential treatment in a population of patients with chronic kidney disease as well as in animal models (34,36). This literature demonstrates that widespread studies are ongoing examining the potential benefits of angiotensin receptor-neprilysin inhibition in renal and cardiovascular diseases.…”
Section: Data Inmentioning
confidence: 99%
“…The study report of the PARADIGM trial highlighted the role of NEP inhibitors in the population of heart failure with reduced ejection fraction [14] . In an in-vivo study of subtotal nephrectomy, the renoprotective effect of sacubitril/valsartan was found to be stronger as compared to valsartan alone [15] . According to the result of the U.K. HARP-III trial, the combination of sacubitril/valsartan is effective and is well-tolerated in the chronic kidney disease population [16] .…”
Section: Introductionmentioning
confidence: 92%